Design Optimization of Radio Frequency Discrete Tuning Varactors - Mendes, Luís (2009)
This work presents a procedure to automate the design of Si-integrated radio frequency (RF) discrete tuning varactors (RFDTVs). The synthesis method, which is based on evolutionary algorithms, searches for optimum performance RF switched capacitor array circuits that fulfill the design restrictions. The design algorithm uses the -dominance concept and the maximin sorting scheme to provide a set of different solutions (circuits) well distributed along an optimal front in the parameter space (circuit size and component values). Since all the solutions present the same performance, the designer can select the circuit that is best suited to be implemented in a particular integration technology. To assess the performance of the synthesis procedure, several RFDTV circuits, provided by the algorithm, were designed and simulated using a 0.18μm CMOS technology and the Cadence Virtuoso Design Platform. The comparisons between the algorithm and circuit simulation results show that they are very close, pointing out that the proposed design procedure is a powerful design tool.